Pengaruh Nilai Kohesi Tanah Terhadap Stabilitas Retaining Wall Pada Basement Gedung Bertingkat - Putri, Feby Aristia; Adha, Idharmahadi; Setyanto, Setyanto (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2016)
This study aims to determine the stability of the retaining wall as a basement storey building in the city of Bandar Lampung. This study uses secondary data, ie, bor logs and SPT. Data on. laboratory test results are obtained from the geotehnical report.Based on the geotechnical data on the stability calculation and reinforcement retaining wall. High retaining wall is 3.25 meters with a thickness of 0.6 meters and a width 1meter (reviewed per meter). Calculation of the stability of retaining wall just reviewed against the danger of sliding and rolling hazard. As for reinforcing the retaining wall of concrete is based on ISO 2013.From the analysis, obtained the value of stability to the danger of sliding and rolling 4.8 ≥ 1.5 were declared safe retaining wall against the danger of sliding and rolling. The results of calculations on the retaining wall reinforcement, for the main reinforcement D16 - 250, shear D13 - 200, and reinforcement for D10-300. Amount of reinforcement based on the calculation is similar to the design of reinforcement used in the construction of this multi-storey building.  Keywords: retaining wall, basement, shear stability and bolsters.